Granulocytic myeloid‐derived suppressor cells inversely correlate with plasma arginine and overall survival in critically ill patients. (May 2015) - Gey, A.; Tadie, J.‐M.; Caumont‐Prim, A.; Hauw‐Berlemont, C.; Cynober, L.; Fagon, J.‐Y.; Terme, M; Diehl, J.‐L.; Delclaux, C.; Tartour, E.
Summary Critically ill patients display a state of immunosuppression that has been attributed in part to decreased plasma arginine concentrations. However, we and other authors have failed to demonstrate a clinical benefit of L‐arginine supplementation. We hypothesize that, in these critically ill patients, these low plasma arginine levels may be secondary to the presence of granulocytic myeloid‐derived suppressor cells (gMDSC), which express arginase known to convert arginine into nitric oxide (NO) and citrulline. Indeed, in a series of 28 non‐surgical critically ill patients, we showed a dramatic increase in gMDSC compared to healthy subjects (P = 0·0002). A significant inverse correlation was observed between arginine levels and gMDSC (P = 0·01). As expected, gMDSC expressed arginase preferentially in these patients. Patients with high gMDSC levels on admission to the medical intensive care unit (MICU) presented an increased risk of death at day 7 after admission (P = 0·02). In contrast, neither plasma arginine levels, monocytic MDSC levels nor neutrophil levels were associated with overall survival at day 7. No relationship was found between body mass index (BMI) or simplified acute physiology score (SAPS) score, sequential organ failure assessment (SOFA) score or gMDSC levels, eliminating a possible bias concerning the direct prognostic role of these cells. As gMDSC exert their immunosuppressive activity via multiple mechanisms [production of prostaglandin E2 (PGE2), interleukin (IL)‐10, arginase, etc.], it may be more relevant to target these cells, rather than simply supplementing with L‐arginine to improve immunosuppression and its clinical consequences observed in critically ill patients.